Tinjauan Pustaka: Patofisiologi, Diagnosis, dan Tatalaksana Rinitis Alergi - Ahmad Duta Al-Ihya; Ghina Salsabila Fenty PNR; Putu Ristyaning Ayu Sangging; Rani HImayani (CV. Jasa Sukses Abadi, 2023)
Rhinitis is broadly defined as inflammation of the nasal mucosa. The incidence rate of allergic rhinitis in Indonesia is estimated at approx 10-20% and soon increase. The average age of allergic rhinitis is 8-11 years,and 80% allergic rhinitis occurs in 20 years old. Rhinitis describes a pattern of symptoms resulting from nasal inflammation and/or nasal mucosal dysfunction that includes many different subtypes. There are three different, widely accepted subtypes of rhinitis: allergic rhinitis, infectious rhinitis, and non-allergic rhinitis, non-infectious rhinitis. Rhinitis is characterized by the presence of one or more of the following nasal symptoms: nasal congestion, anterior or posterior rhinorrhea, sneezing, and pruritus.The diagnosis of this disease can be done by percutaneous skin tests (skin prick test), radioalergosorbent test (RAST), simultaneous multiantigen test (MAST), fluoroallergosorbent test (FAST), and capture immunoassay test (ImmunoCAP). A thorough medical history and detailed clinical examination may lead to suspicion of allergic rhinitis. Medical therapy includes intranasal corticosteroids, which are safe to administer to both adults and children and are superior to combination oral antihistamines and leukotriene receptor antagonists. The first generation antihistamines are no longer recommended because of side effects, whereas the second generation oral antihistamines have strong H1 receptor selectivity and weak anticholinergic action. Nasal irrigation is widely used in all types of rhinitis with isotonic or hypertonic saline and helps remove mucus and clears inflammatory medications.